Investigating the Utilization of Vocabulary Builder Courseware in Broadening EFL Learners’ Vocabulary Mastery - Nurmahati, Izza Aisyah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
The mastery of vocabulary is a crucial component of language learning, particularly in the context of English as a Foreign Language (EFL). A strong vocabulary foundation not only facilitates better comprehension and communication but also enables learners to engage more deeply with the language. However, expanding one''s vocabulary in a non-native language presents significant challenges, often requiring innovative instructional methods to enhance learning outcomes. In recent years, Vocabulary Builder courseware has emerged as a promising tool in the educational technology landscape, offering structured and interactive approaches to vocabulary acquisition. This research employed qualitative method in analyzing the data from the questionnaire. Teaching a language also highly needs technology assistance to make it easier and more effective. By combining both traditional method and technology, many research have proven that it is more way better than just using the traditional one. To that reason, teaching a vocabulary through a courseware will give a great result since it is not only emphasized in introducing a new word but also pronunciation is promoted.